Analisis Implementasi Pensertifikatan Aset Tanah Pemerintah Daerah Kabupaten Langkat - Medaline, Onny; Nurhilmiyah; Syafriana, Rizka (Universitas Medan Area, 2024)
Regional property is regional assets obtained from the APBD or other acquisitions. The security of state/regional property only started in 2004, marked by the promulgation of the State Treasury Law. State/regional property in the form of land controlled by the Central/Regional Government must be certified in the name of the Government/Regional Government. The research results in this paper include a study of regional asset certification in the land law regime and regional government, as well as a description of the implementation of land asset certification in the Langkat Regency regional government. The aim of this research is to determine the normative and implementation context of certifying regional assets in the form of land in Langkat Regency. The research method used is empirical research with an approach that emphasizes collecting data obtained from facts in the field. The results of this research indicate that land law and state treasury law in the study of state and regional assets in the form of land need to complement each other to create legal certainty. Regional asset certification in Langkat Regency has been implemented, but has not yet reached 50% of the land plots. In the process of certifying BMD land rights, BPKAD found several obstacles related to other ministries, for example: the process of releasing HGU land from PTPN II is still hampered, which must comply with several provisions from the Ministry of BUMN regarding the transfer of BUMN fixed assets